Composite sintered body, electrostatic chuck member, and electrostatic chuck device
By introducing nitrogen atoms into the aluminum oxide main phase ceramic composite of the electrostatic adsorption device and controlling the content of calcium silicate, the contradiction between high dielectric constant and low wear in the prior art is solved, and efficient electrostatic adsorption and durability improvement are achieved.
Patent Information
- Application Number
- JP2023161529
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-04-07
AI Technical Summary
The prior art is difficult to suppress wear of electrostatic adsorption devices while maintaining a high dielectric constant, resulting in problems of abnormal discharge and equipment damage under high-voltage cooling conditions.
Aluminum oxide main phase ceramic composite using a small amount of calcium silicate containing nitrogen atoms as the secondary phase material increases the relative dielectric constant of the composite by introducing nitrogen atoms at the grain interface, while controlling the content of calcium silicate to reduce wear.
It realizes the reduction of wear of the electrostatic adsorption device while maintaining a high relative dielectric constant, improves the durability and stability of the device, and avoids abnormal discharge and equipment damage.
Smart Images

Figure 2025052690000002 
Figure 2025052690000003 
Figure 2025052690000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite sintered body, an electrostatic chuck member, and an electrostatic chuck device. [Background technology]
[0002] In semiconductor manufacturing equipment that performs plasma processes, an electrostatic chuck device is used that can easily attach and fix a plate-shaped sample (wafer) to a sample stage and can maintain the wafer at a desired temperature. The electrostatic chuck device is equipped with a base body, one main surface of which is a mounting surface on which a wafer is placed, and an electrostatic attraction electrode that generates an electrostatic force (Coulomb force) between the wafer placed on the mounting surface (see, for example, Patent Document 1). The base body is usually made of a ceramic sintered body.
[0003] A known configuration of an electrostatic chuck device is to provide a fine groove in the sample stage and supply a gaseous coolant (e.g., helium) to the groove to allow the coolant to flow between the wafer and the sample stage. In such an electrostatic chuck device, the coolant flowing in the groove cools the wafer, reducing the temperature difference within the wafer surface and making it possible to maintain the wafer at a desired temperature.
[0004] In such an electrostatic chuck device, it is conceivable that the cooling efficiency can be improved and the temperature difference within the wafer surface can be reduced by increasing the gas pressure (supply pressure) of the coolant supplied to the groove of the sample table. When the gas pressure of the coolant is increased in the electrostatic chuck device having the above configuration, the electrostatic chuck device is required to have a high chucking force so that the wafer does not become detached due to the pressure from the coolant. In order to obtain a high chucking force, it is preferable that the relative dielectric constant of the base of the electrostatic chuck device is high.
[0005] On the other hand, the electrostatic chuck device is exposed to an AC electric field for generating plasma during a plasma process, and the base is preferably made of a material with a low dielectric tangent in order to suppress heat generation in the AC electric field.
[0006] As a base for an electrostatic chuck device that combines a high relative dielectric constant and a low dielectric tangent, a composite sintered body of ceramics containing a metal oxide as a main phase and silicon carbide as a subphase, in which a predetermined amount of silicon carbide crystal grains are dispersed within the crystal grains of the metal oxide and at the crystal grain boundaries of the metal oxide, has been proposed (see, for example, Patent Document 2). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2005-210077 A [Patent Document 2] International Publication No. 2018 / 181130 Summary of the Invention [Problem to be solved by the invention]
[0008] In order to increase the relative dielectric constant of the compound sintered body described in Patent Document 2, the content of electrically conductive silicon carbide can be increased. However, if the content of silicon carbide is increased, the base formed of the compound sintered body is likely to be worn due to friction between the wafer and the base when the wafer is placed on the base. If the base is worn, there is a risk of problems such as abnormal discharge occurring during the plasma process due to foreign matter generated by the wear, causing damage to the device, or an increase in the temperature difference within the wafer surface.
[0009] On the other hand, the wear of the base body can be suppressed by reducing the content of silicon carbide in the compound sintered body described in Patent Document 2. However, in this case, the relative dielectric constant of the base body (compound sintered body) decreases, and the chucking force of the electrostatic chuck device decreases.
[0010] Therefore, there has been a demand for a composite sintered body that can form a substrate having a high relative dielectric constant even with a small silicon carbide content.
[0011] The present invention has been made in view of the above circumstances, and has an object to provide a novel compound sintered body having a high relative dielectric constant, and a further object to provide an electrostatic chuck member and an electrostatic chuck device using such a compound sintered body. [Means for solving the problem]
[0012] In order to solve the above problems, one aspect of the present invention includes the following aspects.
[0013] [1] A ceramic composite sintered body including an aluminum oxide main phase and a silicon carbide subphase, the composite sintered body further including nitrogen atoms, the nitrogen atom content being 0.015% by mass or more and 0.030% by mass or less.
[0014] [2] The composite sintered body according to [1], wherein the nitrogen atoms are present at interfaces between the aluminum oxide crystal grains and the silicon carbide crystal grains.
[0015] [3] The composite sintered body according to [1] or [2], wherein the content of the silicon carbide is 1 part by mass or more and 7.5 parts by mass or less per 100 parts by mass of the aluminum oxide.
[0016] [4] An electrostatic chuck member comprising: a plate-shaped base, one main surface of which is a mounting surface for mounting a plate-shaped sample, the plate-shaped base being made of the composite sintered body according to [1] or [2] as a forming material; and an electrostatic adsorption electrode provided on the side of the base opposite to the mounting surface or inside the base.
[0017] [5] An electrostatic chuck device comprising the electrostatic chuck member according to [4]. Effect of the Invention
[0018] According to the present invention, it is possible to provide a novel compound sintered body having a high relative dielectric constant, and also to provide an electrostatic chuck member and an electrostatic chuck device using such a compound sintered body. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a schematic diagram showing the state of a sintered body when measuring the volume resistivity. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing a preferred example of the electrostatic chuck device of the present embodiment. [Diagram 3] FIG. 3 is a photograph showing a BF-STEM image of Example 3. [Figure 4] FIG. 4 is a diagram showing the results of EDX analysis of the interface between aluminum oxide and silicon carbide in Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, each embodiment of the composite sintered body, electrostatic chuck member, and electrostatic chuck device of the present invention will be described. The present embodiment is specifically described to better understand the gist of the invention, and does not limit the present invention unless otherwise specified. For example, unless otherwise limited, conditions such as materials, amounts, types, numbers, sizes, ratios, and temperatures may be changed, added, or omitted as necessary. Preferred examples may be exchanged or shared between the embodiments described below.
[0021] {Composite sintered body} The composite sintered body of the present embodiment is a ceramic composite sintered body including aluminum oxide (Al2O3) as a main phase and silicon carbide (SiC) as a subphase. The composite sintered body further includes nitrogen atoms, and the content of the nitrogen atoms in the composite sintered body is 0.015% by mass or more and 0.030% by mass or less.
[0022] In the compound sintered body, the nitrogen atoms may be present at the interface between the Al2O3 crystal grains and the SiC crystal grains. More specifically, in the compound sintered body, the SiC crystal grains are present at the grain boundaries of the Al2O3 phase, and a small amount of nitrogen atoms may be present at the interface between the Al2O3 phase and the SiC particles present at the grain boundaries of the Al2O3 phase.
[0023] Although the details are unclear, the compound sintered body of the present embodiment contains a trace amount of nitrogen atoms, and thus has a higher dielectric constant than a compound sintered body that does not contain nitrogen atoms. The inventors speculate that the presence of nitrogen atoms forms a conductive path inside the compound sintered body.
[0024] Here, "the dielectric constant is improved compared to a compound sintered body that does not contain nitrogen atoms" means that the dielectric constant is higher than that of a compound sintered body with the same SiC content.
[0025] The nitrogen atom content in the compound sintered body is 0.015% by mass or more and 0.030% by mass or less, preferably 0.018% by mass or more and 0.027% by mass or less, and may be 0.019% by mass or more and 0.026% by mass or less. The upper and lower limits of the nitrogen atom content can be combined in any desired manner.
[0026] It is believed that the compound sintered body has a nitrogen atom content of 0.015 mass% or more, which makes it easier to form conductive paths within the compound sintered body and improves the relative dielectric constant. On the other hand, the compound sintered body has a nitrogen atom content of 0.030 mass% or less, which increases the relative density of the compound sintered body and improves the plasma resistance and voltage resistance characteristics.
[0027] The nitrogen content in the composite sintered body can be measured by the inert gas fusion-infrared absorption method and the inert gas fusion-thermal conductivity method. The measurement device used is an oxygen / nitrogen / hydrogen analyzer (LECO, TCH600 model).
[0028] In the composite sintered body, the presence of nitrogen atoms at the interface between the Al2O3 crystal grains and the SiC crystal grains can be confirmed by using a bright-field image (BF-STEM image) of a scanning transmission electron microscope (STEM). In the same field of view as the BF-STEM image, EDX analysis is performed on the interface between the SiC particles at the grain boundaries of the Al2O3 phase and the Al2O3 phase. If a nitrogen peak is detected, it indicates the presence of nitrogen, and if no nitrogen peak is detected, it indicates the absence of nitrogen.
[0029] The nitrogen atoms are present at the interfaces between the Al2O3 crystal grains and the SiC crystal grains in an amount sufficient to obtain a desired dielectric constant, but may also be present at locations other than the interfaces.
[0030] The composite sintered body may further contain an aluminum silicate. The silicate is generated by a reaction between an oxide film (SiO2 film) on the surface of a SiC particle and an Al2O3 particle. The SiO2 film will be described later. The silicate is Al8O 12 Si2 and Al7O 14 Examples of such mullite include Si2.
[0031] The Al2O3, SiC, and silicate that make up the compound sintered body are each dispersed throughout the compound sintered body, and also aggregate in various places in the compound sintered body to form the Al2O3 phase, SiC phase, and silicate phase. Of these phases, the silicate phase has the lowest durability against plasma. Therefore, when a compound sintered body containing a silicate phase is exposed to plasma, the silicate phase is most likely to be damaged.
[0032] Therefore, when the compound sintered body contains a silicate phase (aggregates containing silicate), it is preferable that the average aggregate diameter of the silicate phase is 5 μm or less. The average aggregate diameter of the silicate phase can be calculated as the arithmetic average of the long side lengths of the smallest rectangle circumscribing the aggregates. The average aggregate diameter of the silicate phase can be calculated from an electron microscope image such as an SEM image. By having the average aggregate diameter of the silicate phase be 5 μm or less, it becomes difficult to be locally subjected to large plasma erosion, and the service life of the electrostatic chuck device can be extended.
[0033] (Dielectric constant) The dielectric constant of the compound sintered body at 200 Hz is preferably 11 or more, more preferably 12.0 or more, and even more preferably 12.5 or more. When the dielectric constant of the compound sintered body at 200 Hz is 11 or more, it is possible to generate an electrostatic adsorption force sufficient to adsorb a wafer to an electrostatic chuck device. The upper limit of the dielectric constant at 200 Hz is not particularly limited, and may be 60 or less, 50 or less, 25 or less, or 20 or less.
[0034] From the viewpoint of improving the withstand voltage of the electrostatic chuck member including the composite sintered body, the relative dielectric constant at 200 Hz is preferably equal to or less than 25, and more preferably equal to or less than 20. The upper and lower limit values of the relative dielectric constant at 200 Hz can be combined in any desired manner.
[0035] The dielectric constant of the compound sintered body at 1 MHz is preferably 11 or more and 40 or less, and more preferably 12 or more and 30 or less. When the dielectric constant of the compound sintered body at 1 MHz is within the above range, it is possible to generate an electrostatic adsorption force sufficient to adsorb a wafer to an electrostatic chuck device.
[0036] From the viewpoint of improving the withstand voltage of the electrostatic chuck member including the composite sintered body, the relative dielectric constant at 1 MHz is preferably equal to or less than 23, and more preferably equal to or less than 20. The upper and lower limit values of the relative dielectric constant at 1 MHz can be combined in any desired manner.
[0037] The relative dielectric constant of the composite sintered body means a value measured by the parallel plate method using an impedance analyzer (model number: E4990A, manufactured by Keysight Technologies) and an LCR meter (model number: 4274A, manufactured by Keysight Technologies) in air at room temperature (25°C). When measuring the dielectric constant of a composite sintered body, a test piece of the composite sintered body with a constant size and thickness may be used. For example, a cylindrical test piece with a diameter of 28 mm and a thickness of 1 mm may be used, or a rectangular parallelepiped test piece with a size of 56 mm x 56 mm x 2 mm may be used.
[0038] (Volume resistivity) The volume resistivity (Ω cm) of the composite sintered body is 1.0×10 15 Ω cm or more 1.0×10 18 It is preferable that the resistance is Ω·cm or less, and 1.0×10 16 Ω cm or more 1.0×10 17 When the volume resistivity of the composite sintered body is in the above range, the insulating properties as the base of the electrostatic chuck device are sufficient, and an increase in leakage current to the attracted wafer can be suppressed, and the destruction of the device formed on the wafer and the failure of the wafer to be detached can be suppressed.
[0039] The volume resistivity (Ω·cm) of the composite sintered body is a value measured by a direct current three-terminal method. Figure 1 is a schematic diagram showing the state of the sintered body when measuring the volume resistivity. In the figure, reference numeral 100 denotes the sintered body, reference numeral 110 denotes the main electrode, reference numeral 120 denotes the guard electrode, and reference numeral 130 denotes the counter electrode.
[0040] A screen printer is used to print silver paste (US-202A, manufactured by Daiken Chemical Manufacturing and Sales Co., Ltd.) on the upper and lower surfaces of the sintered body 100, and the resulting product is dried in air at 150° C. for 12 hours to form the main electrode 110, the guard electrode 120, and the counter electrode 130. As the screen printer, for example, MEC-2400 manufactured by Mitani Micronics Co., Ltd. can be used.
[0041] A DC voltage is applied to the sintered body with the three electrodes formed, and the current after charging for one minute is measured to determine the volume resistance (Rv) of the sintered body. Next, the volume resistivity (ρv) is calculated from the thickness of the sintered body and the area of the electrodes using the following formula (1). ρv = S / t × Rv = S / t × V / I … (1) (S: effective area of electrode (cm 2 ), t: thickness of sintered body (cm), Rv: volume resistance (Ω), V: DC voltage (V), I: current (A)
[0042] The volume resistivity can be measured using, for example, a resistivity measuring device manufactured by Nishiyama Seisakusho Co., Ltd. and a digital ultra-high resistance / microammeter manufactured by ADC Corporation.
[0043] (composition) In the compound sintered body, the ratio of Al2O3 to SiC is not particularly limited as long as the desired dielectric constant and volume resistivity are obtained. For example, the ratio of SiC is 1 part by mass or more and 10 parts by mass or less per 100 parts by mass of Al2O3.
[0044] From the viewpoint of improving the wear resistance and voltage resistance of the compound sintered body, the content of SiC relative to 100 parts by mass of Al2O3 is preferably 1 part by mass or more and 7.5 parts by mass or less, and more preferably 2 parts by mass or more and 6 parts by mass or less.
[0045] It is known that SiC has many crystal structures. Specifically, there are those having a 3C type (zinc blende type) crystal structure in a cubic crystal system, those having a wurtzite type crystal structure in a hexagonal crystal system such as 4H type or 6H type, and those having a 15R type crystal structure in a rhombohedral crystal system. In this embodiment, those having the 3C type crystal structure are referred to as "β-SiC". All those having other crystal structures are referred to as "α-SiC".
[0046] The SiC contained in the compound sintered body is preferably β-SiC. In addition, in the compound sintered body, it is preferable that the β-SiC crystal grains are surrounded by the crystal grains of Al2O3, which is the matrix material, that is, are dispersed within the crystal grains of Al2O3.
[0047] The term "wear resistance" means that the compound sintered body is not easily worn down by physical contact. The excellent wear resistance of the compound sintered body suppresses wear caused by repeated contact with a wafer, and also suppresses wear when exposed to plasma. As a result, the compound sintered body with excellent wear resistance can extend the service life of an electrostatic chuck member and an electrostatic chuck device made of such a compound sintered body.
[0048] The method for evaluating the wear resistance is not particularly limited, but for example, it can be evaluated based on the resistance to cutting in mechanical processing.
[0049] (Voltage resistance) The withstand voltage of the compound sintered body means the voltage (withstand voltage) at which a current of 1 μA flows through a test piece of the sintered body when a voltage is applied to the compound sintered body at a rate of 1 kV / sec. The thickness of the compound sintered body is not particularly limited, and can be measured at a thickness of, for example, 0.3 mm.
[0050] (crystal grain size) The average crystal grain size of the Al2O3 particles contained in the compound sintered body can be selected as long as the compound sintered body satisfies the above-mentioned electrical properties (dielectric constant, volume resistivity, and withstand voltage), but is preferably 1.2 μm to 10 μm, more preferably 1.5 μm to 5 μm, and even more preferably 1.7 μm to 3 μm.
[0051] In the composite sintered body, the average crystal grain size of the Al2O3 particles is 1.2 μm or more, so that the resistivity of the Al2O3 particles themselves does not decrease too much, and a sufficient insulating effect can be exhibited. Also, the average crystal grain size of the Al2O3 particles is 10 μm or less, so that the mechanical strength of the obtained sintered body is sufficiently high and chipping is unlikely to occur.
[0052] In the compound sintered body, the average crystal grain size of Al2O3 can be adjusted by controlling the sintering temperature. When the sintering temperature is high, the average crystal grain size of Al2O3 tends to become large, and when the sintering temperature is low, the average crystal grain size of Al2O3 tends to become small.
[0053] (Metal impurities) In the composite sintered body, the content of metal impurities other than aluminum and silicon is preferably 100 ppm or less, more preferably 50 ppm or less, and even more preferably 25 ppm or less.
[0054] <<Method for manufacturing a compound sintered body>> The method for producing the compound sintered body of the present embodiment includes the steps of: (a) a pre-oxidation step of oxidizing the surface of SiC particles; (b) a step of injecting the SiC particles treated in the pre-oxidation step and the Al2O3 particles, respectively, and mixing them while colliding with each other to obtain a slurry containing a dispersion medium; (c) adding a dispersant to the slurry and then adjusting the pH of the slurry so that the surface charge of the Al2O3 particles in the slurry is positive and the surface charge of the SiC particles in the slurry is negative; (d) removing the dispersion medium from the pH-adjusted slurry to obtain granules containing Al2O3 particles and SiC particles; (e) heating the obtained granules in a non-oxidizing atmosphere at 300° C. or more and 600° C. or less, and then heating the granules in an oxidizing atmosphere to oxidize the surfaces of the granules; (f) forming the oxidized granules into a molded body; (g) A step of heating the obtained green body to 1600° C. or higher while compressing it at a pressure of 5 MPa or more in a nitrogen atmosphere, thereby pressure sintering it.
[0055] The "non-oxidizing atmosphere" can be selected arbitrarily, but preferred examples include an inert gas atmosphere and a vacuum atmosphere.
[0056] The inert gas can be selected arbitrarily, and for example, nitrogen and / or argon can be preferably used. The "nitrogen atmosphere" may contain inert gases other than nitrogen as long as the purpose and effects of the present invention are not impaired.
[0057] "Vacuum" refers to "a state in a space filled with gas at a pressure lower than atmospheric pressure" and is a state defined in the JIS standard as a pressure that can be used industrially. A vacuum atmosphere refers to an atmosphere in which the pressure of the atmospheric gas is the above-mentioned "vacuum." In this embodiment, the vacuum atmosphere may be a low vacuum (100 Pa or more), but is preferably a medium vacuum (0.1 Pa to 100 Pa), and more preferably a high vacuum (10-5 It is more preferable that the pressure is in the range of 0.1 Pa to 0.1 Pa.
[0058] The oxidizing atmosphere may mean that the atmospheric gas contains oxygen. Examples of the oxidizing atmosphere include air atmosphere and a mixed gas atmosphere of an inert gas and oxygen.
[0059] In the manufacturing method of the compound sintered body of this embodiment, the Al2O3 particles used preferably have an Al2O3 content of 99.99% or more. Such high-purity Al2O3 particles can be prepared by using the alum method. The Al2O3 particles prepared by the alum method can have a significantly reduced content of sodium atoms, which are metal impurities, compared to Al2O3 particles prepared by, for example, the Bayer method. In addition, various other methods can be adopted as long as Al2O3 particles of the desired purity can be obtained.
[0060] (a) Pre-oxidation process In the pre-oxidation step, first, the SiC particles used as the raw material are subjected to a heat treatment in an oxidizing atmosphere to preliminarily oxidize the surfaces of the SiC particles. Hereinafter, the above-mentioned oxidation treatment may be referred to as "pre-oxidation".
[0061] The average particle diameter of the SiC particles used can be selected arbitrarily as long as it can be processed by the grinding and mixing device described later, but is preferably 20 to 100 nm, and more preferably 35 to 80 nm. The upper and lower limit values of the average particle diameter of the SiC particles can be arbitrarily combined. However, it is not limited to these examples. The average particle diameter may be the length average diameter of the particles. That is, the average particle diameter of the SiC particles may be the arithmetic average value of the length of the long side of the smallest rectangle circumscribing the SiC particles. The average particle diameter of SiC can be calculated from an electron microscope image such as SEM.
[0062] The temperature and time of pre-oxidation are not particularly limited as long as the effects of the present invention can be obtained, and the temperature is, for example, preferably 200 to 550°C, and more preferably 250 to 500°C. The upper and lower limit values of the pre-oxidation temperature can be combined arbitrarily. The time of pre-oxidation is, for example, preferably 1 to 24 hours, and more preferably 6 to 12 hours. The upper and lower limit values of the pre-oxidation time can be combined arbitrarily. However, they are not limited to these examples.
[0063] In the pre-oxidation step, the surfaces of the SiC particles can be oxidized, for example, by heating at 500° C. for 12 hours. When the content of SiC particles is high, the pre-oxidation temperature is preferably 200° C. or higher and 450° C. or lower, and more preferably 250° C. or higher and 400° C. or lower. By lowering the pre-oxidation temperature, a composite sintered body with excellent wear resistance can be obtained.
[0064] By pre-oxidizing the SiC particles, a silicon oxide (SiO2) film is generated on the surface of the SiC particles. As a result, the hydrophilicity of the SiC particles is increased. This improves the dispersibility of the SiC particles in the slurry.
[0065] ((b) Step of obtaining slurry) In the mixing step to obtain a slurry, a grinding mixer, for example, a two-flow particle collision type grinding mixer, is used. A dispersion medium is prepared, and Al2O3 particles and pre-oxidized SiC particles are dispersed. Using the grinding mixer, the dispersion liquid is pressurized and sprayed at high speed, and the Al2O3 particles and SiC particles are mixed while colliding with each other. This mixing pulverizes the Al2O3 particles and SiC particles, and a dispersion liquid (slurry) containing pulverized particles of these particles is obtained. The spray speed can be selected arbitrarily, but is preferably, for example, 300 ml / min to 550 ml / min.
[0066] The average particle size of the Al2O3 particles used as the raw material can be selected arbitrarily as long as it can be processed by a grinding and mixing device, but for example, it is preferably 0.05 to 0.3 μm, and more preferably 0.1 to 0.25 μm. The upper and lower limit values of the average particle size of the Al2O3 particles can be arbitrarily combined.
[0067] The amount of SiC particles used, i.e., the content of SiC particles in the resulting slurry, is preferably 1 part by mass or more and 10 parts by mass or less, more preferably 2 parts by mass or more and 7.5 parts by mass or less, relative to 100 parts by mass of Al2O3 particles. The upper limit and lower limit of the amount of SiC particles can be arbitrarily combined. However, they are not limited to these examples.
[0068] The dispersion medium to be used can be any solvent in which Al2O3 particles and SiC particles can be dispersed, and examples of the dispersion medium include water and alcohols such as methanol, ethanol, etc. These dispersion media may be used alone or in combination of two or more.
[0069] When Al2O3 particles and SiC particles collide, larger particles have a large kinetic energy at the time of collision and are easily pulverized. On the other hand, smaller particles have a small kinetic energy at the time of collision and are not easily pulverized. Therefore, the pulverized Al2O3 particles and SiC particles obtained using the above-mentioned pulverizing and mixing device have a narrow particle size distribution width with few coarse particles and over-pulverized particles. Therefore, if the mixed particles pulverized and mixed using the two-flow particle collision type pulverizing and mixing device are used, abnormal grain growth with coarse particles as nuclei can be suppressed in the sintering process.
[0070] In addition, when grinding and mixing using such a grinding and mixing device, it is possible to suppress the inclusion of impurities due to breakage of each media, compared to a method of grinding and mixing using media such as a ball mill or a bead mill.
[0071] ((c) pH Adjustment Step) In the step of adjusting the pH, the pH of the slurry is adjusted taking into consideration the surface charge of the Al2O3 particles and the SiC particles in the slurry. The slurry obtained in the above mixing step (slurry before pH adjustment) usually exhibits a basicity of about pH 11.
[0072] When the pH of the slurry is on the acidic side (pH<7), the ζ potential of the Al2O3 particles is positive. This is because when the pH of the slurry is on the acidic side, the hydroxyl groups on the surface of the Al2O3 particles are converted to protons (H + ) and the surface becomes positively charged.
[0073] On the other hand, when the pH of the slurry is basic (pH > 7), the ζ potential of the Al2O3 particles becomes negative. This is because when the pH of the slurry is basic, protons are dissociated from the hydroxyl groups on the surface of the Al2O3 particles, and the surfaces become negatively charged.
[0074] In contrast, the ζ-potential behavior of SiC particles is different. When the pH of the slurry is 2 to 3, the ζ-potential of SiC particles is 0, and when the pH of the slurry is in the acidic region around 3 to the basic region, the ζ-potential becomes negative.
[0075] When two particles with such a relationship coexist in the same slurry, the two particles will aggregate, a phenomenon known as hetero-aggregation, in the range of the pH of the system where "the surface charge of the Al2O3 particles in the slurry is positive" and "the surface charge of the SiC particles in the slurry is negative." In this process, the pH of the slurry is adjusted to about 2.6 to 7.5 to cause hetero-aggregation of the Al2O3 particles and the SiC particles.
[0076] At this time, it is preferable to add a suitable dispersant to the slurry so that the Al2O3 particles and the SiC particles do not precipitate. As the dispersant, a known dispersant, for example, a polycarboxylic acid-based dispersant, can be used. As the dispersant, a commercially available product can be preferably used, for example, Aron A6114 (manufactured by Toa Gosei Co., Ltd.).
[0077] The pH of the slurry during hetero-aggregation is preferably from 3 to 7, more preferably from 5 to 7, and even more preferably from 6 to 7. When comparing the ζ-potentials of both particles after pH adjustment, the closer the absolute values of the ζ-potentials are, the easier hetero-aggregation will occur, resulting in a desired aggregated state.
[0078] The pH can be adjusted by adding an acid to the slurry. Preferred examples of acids that can be used include inorganic acids such as nitric acid, phosphoric acid, hydrochloric acid, and sulfuric acid, and organic acids such as acetic acid. Among these, hydrochloric acid, sulfuric acid, and the like may generate chlorine and sulfur in the apparatus during the sintering step described below, which may cause deterioration of the apparatus. Therefore, it is preferable to use nitric acid, phosphoric acid, and organic acids to adjust the pH.
[0079] ((d) Step of obtaining granules) In the step of obtaining granules, the dispersion medium is removed from the pH-adjusted slurry to obtain granules containing Al2O3 particles and SiC particles. The method for removing the dispersion medium can be selected arbitrarily, and for example, a known spray drying method can be suitably used. The size of the granules can be selected arbitrarily, but generally, it may be, for example, 30 to 100 μm or 50 to 85 μm.
[0080] In the spray-drying method, minute droplets of slurry are sprayed to increase the surface area per unit volume of the slurry, and the minute droplets are continuously exposed to hot air, allowing for instant drying and granulation. Granules produced by the spray-drying method tend to be spherical, reflecting the shape of the minute droplets.
[0081] ((e) Oxidation treatment step) In the oxidation treatment step, treatment is carried out successively under two atmospheres.
[0082] First, the obtained granules are heated to 300°C to 600°C (for example, 500°C) under normal pressure (without pressing) in a non-oxidizing atmosphere. This removes impurities such as moisture, dispersion medium, and dispersant contained in the granules. The temperature may be 300 to 400°C, 400 to 500°C, or 500 to 600°C, as necessary. The heating time can be selected arbitrarily, and may be, for example, 3 to 8 hours, 8 to 10 hours, or 10 to 15 hours.
[0083] As the non-oxidizing atmosphere, an inert gas atmosphere using nitrogen or argon is preferable. When the heating is performed under an inert gas atmosphere, it is preferable to perform the heating treatment under a so-called gas flow in which the atmospheric gas is made to flow in order to efficiently discharge the generated impurities outside the system.
[0084] Next, the granules from which the impurities have been removed are heated to an arbitrary temperature (for example, 400°C) in an oxidizing atmosphere to carry out an oxidation treatment. The atmosphere for the oxidation treatment can be arbitrarily selected, but is preferably an air atmosphere. The above temperature can be selected as necessary, and may be 250 to 370°C, 300 to 500°C, or 400 to 600°C, for example. The heating time can be arbitrarily selected, and may be, for example, 1 to 5 hours, 5 to 12 hours, or 12 to 24 hours.
[0085] According to such an operation, an oxide film (SiO2 film) is formed on the surface of the SiC particles contained in the granules during the oxidation treatment. Metal impurities contained in the granules are likely to dissolve into the oxide film. Therefore, the metal impurities contained in the granules are concentrated on the granule surface. In this case, it is preferable because the metal impurities are easily removed in the pressure sintering process described later.
[0086] In addition, when the granules are subjected to an oxidation treatment, the surfaces of the SiC particles constituting the granules are more easily oxidized than, for example, when the granules are not subjected to the oxidation treatment and the granules are molded into a molded body (after the step (f) of obtaining a molded body). Therefore, as a result of performing the oxidation treatment before forming the molded body described later, an oxide film is more easily formed evenly on the surfaces of the SiC particles, which is preferable.
[0087] ((f) Step of obtaining a molded body) Next, the resulting granules are molded, preferably by uniaxial molding (uniaxial press molding), according to the desired shape of the sintered body to obtain a molded body.
[0088] ((g) Pressure sintering process) In the pressure sintering step, the compact obtained in the (f) compact obtaining step is heated to 1600°C or higher while being compressed under a pressure of 5 MPa or more, preferably 25 MPa or more, in a nitrogen atmosphere, and pressure sintered. By such an operation, sintering of Al2O3 particles and SiC particles contained in the compact progresses, and a dense sintered body with few pores is obtained. The above temperature can be selected as necessary, and may be 1700 to 1800°C, 1800 to 1900°C, etc. The heating time can be selected arbitrarily, and may be, for example, 1 to 5 hours, 3 to 8 hours, or 6 to 12 hours.
[0089] In this step, pressure sintering is preferably performed in a nitrogen atmosphere at a temperature of 1600° C. to 1850° C. and a sintering pressure in the range of 25 MPa to 50 MPa.
[0090] The compound sintered body produced in this manner absorbs nitrogen molecules (N2) from the atmosphere, becoming a compound sintered body containing nitrogen atoms.
[0091] If the nitrogen atom content in the obtained compound sintered body is not within the target range, it is advisable to adjust the flow rate of nitrogen in the pressure sintering step (g). Increasing the flow rate of nitrogen tends to increase the nitrogen atom content in the compound sintered body.
[0092] The compound sintered body having the above-mentioned structure is a novel compound sintered body having a high relative dielectric constant.
[0093] <Electrostatic chuck member, electrostatic chuck device> 2 is a schematic cross-sectional view showing an electrostatic chuck member 2 and an electrostatic chuck device 1 according to this embodiment. The electrostatic chuck device 1 includes an electrostatic chuck member 2.
[0094] The electrostatic chuck device 1 includes an electrostatic chuck member 2 having a disk shape in plan view with one main surface (upper surface) side as a mounting surface, and a temperature adjustment base part 3 having a disk shape in plan view and a predetermined thickness that is provided below the electrostatic chuck member 2 and adjusts the electrostatic chuck member 2 to a desired temperature. The electrostatic chuck member 2 and the temperature adjustment base part 3 are bonded to each other via an adhesive layer 8 provided between the electrostatic chuck member 2 and the temperature adjustment base part 3. Each part will be explained in turn below.
[0095] <Electrostatic chuck member> The electrostatic chuck member 2 has a mounting plate 11 whose upper surface is a mounting surface 11a on which a plate-like sample W such as a semiconductor wafer is placed, a support plate 12 which is integrated with the mounting plate 11 and supports the bottom side of the mounting plate 11, and an electrostatic attraction electrode 13 provided between the mounting plate 11 and the support plate 12. The electrostatic chuck member 2 may have an insulating layer 14 which insulates the periphery of the electrostatic attraction electrode 13.
[0096] The combined structure of mounting plate 11 and support plate 12 corresponds to the "plate-shaped base" of the present invention.
[0097] In FIG. 2, the electrostatic attraction electrode 13 is provided inside the base (between the mounting plate 11 and the support plate 12), but this is not limited thereto. The electrostatic attraction electrode 13 may be provided on the opposite side of the base from the mounting surface, i.e., below the support plate 12.
[0098] (Placement plate, support plate) The mounting plate 11 and the support plate 12 are disk-shaped members with the same shape of the overlapping surfaces. The mounting plate 11 and the support plate 12 have excellent mechanical strength and durability against corrosive gases and their plasma. The mounting plate 11 and the support plate 12 are made of the above-mentioned composite sintered body.
[0099] A plurality of protrusions 11b each having a diameter smaller than the thickness of the plate-shaped sample are formed at predetermined intervals on the mounting surface 11a of the mounting plate 11. These protrusions 11b support the plate-shaped sample W.
[0100] The overall thickness including the mounting plate 11, support plate 12, electrostatic attraction electrode 13 and insulating layer 14, i.e., the thickness of the electrostatic chuck member 2, can be selected arbitrarily, but is preferably, for example, 0.7 mm or more and 5.0 mm or less.
[0101] For example, when the thickness of the electrostatic chuck member 2 is 0.7 mm or more, it is easy to ensure the mechanical strength of the electrostatic chuck member 2. When the thickness of the electrostatic chuck member 2 is 5.0 mm or less, the heat capacity of the electrostatic chuck member 2 does not become too large, the thermal responsiveness of the plate-shaped sample W placed on it is not deteriorated, and an increase in the lateral heat transfer of the electrostatic chuck member 2 is suppressed, so that it is easy to maintain the in-plane temperature of the plate-shaped sample W at a desired temperature pattern.
[0102] (Electrostatic adhesion electrode) The electrostatic attraction electrode 13 is used to generate an electric charge to generate an electrostatic attraction force and fix the plate-shaped sample W. The shape and size of the electrode 13 are appropriately adjusted depending on the application.
[0103] The electrostatic attraction electrode 13 is formed of a material arbitrarily selected from conductive ceramics and metals that are unlikely to deteriorate or break under the conditions of use of the electrostatic chuck device 1. For example, it is preferable that the electrode 13 be formed of conductive ceramics such as aluminum oxide-tantalum carbide (Al2O3-Ta4C5) conductive composite sintered body, aluminum oxide-tungsten (Al2O3-W) conductive composite sintered body, aluminum oxide-SiC (Al2O3-SiC) conductive composite sintered body, aluminum nitride-tungsten (AlN-W) conductive composite sintered body, aluminum nitride-tantalum (AlN-Ta) conductive composite sintered body, or yttrium oxide-molybdenum (Y2O3-Mo) conductive composite sintered body, or a high-melting point metal such as tungsten (W), tantalum (Ta), or molybdenum (Mo).
[0104] The thickness of the electrostatic attraction electrode 13 can be selected arbitrarily and is not particularly limited. For example, a thickness of 0.1 μm or more and 100 μm or less can be selected, and a thickness of 5 μm or more and 20 μm or less is more preferable.
[0105] If the thickness of the electrostatic attraction electrode 13 is 0.1 μm or more, sufficient conductivity can be ensured. If the thickness of the electrostatic attraction electrode 13 is 100 μm or less, cracks caused by the difference in thermal expansion coefficient between the electrostatic attraction electrode 13 and the mounting plate 11 and the support plate 12 are not formed at the bonding interfaces between the electrostatic attraction electrode 13 and the mounting plate 11 and the support plate 12.
[0106] The electrostatic attraction electrode 13 having such a thickness can be easily formed by a film forming method such as a sputtering method or a vapor deposition method, or a coating method such as a screen printing method.
[0107] (insulation layer) The insulating layer 14 surrounds the electrostatic attraction electrode 13 to protect the electrostatic attraction electrode 13 from corrosive gas and its plasma. The insulating layer 14 is a layer that bonds and integrates the boundary between the mounting plate 11 and the support plate 12, i.e., the outer periphery region other than the electrostatic attraction electrode 13, and is made of an insulating material that has the same composition or the same main component as the material that constitutes the mounting plate 11 and the support plate 12.
[0108] (Temperature control base) The temperature adjustment base part 3 is a thick, disk-shaped member for adjusting the temperature of the electrostatic chuck member 2 to a desired temperature. As the temperature adjustment base part 3, for example, a liquid cooling base or the like having a flow path 3A formed therein for circulating a coolant is suitable.
[0109] There is no particular restriction on the material constituting the temperature adjusting base part 3, so long as it is a metal or a composite material mainly containing these metals, which has excellent thermal conductivity, electrical conductivity, and workability. For example, aluminum (Al), an aluminum alloy, copper (Cu), a copper alloy, stainless steel (SUS), etc. are preferably used as the material constituting the temperature adjusting base part 3. At least the surface of the temperature adjusting base part 3 exposed to plasma is preferably anodized or has an insulating film such as alumina formed thereon.
[0110] An insulating plate 7 may be adhered to the upper surface side of the temperature adjusting base part 3 via an adhesive layer 6 .
[0111] The adhesive layer 6 is made of a heat-resistant and insulating adhesive resin. Examples of such adhesive materials include sheet- or film-shaped polyimide resins, silicone resins, and epoxy resins. The adhesive layer 6 is formed to a thickness of, for example, about 5 to 100 μm.
[0112] The insulating plate 7 is manufactured using an insulating material that is unlikely to deteriorate or break under the usage conditions of the electrostatic chuck device 1. The insulating plate 7 is made of a thin plate, sheet, or film of a heat-resistant resin such as a polyimide resin, an epoxy resin, or an acrylic resin.
[0113] The insulating plate 7 is not limited to a resin sheet or the like, and may be, for example, an insulating ceramic plate or an insulating sprayed film such as alumina.
[0114] (Focus ring) The electrostatic chuck device 1 may have a focus ring 10. The focus ring 10 is a member that is placed on the peripheral portion of the temperature adjustment base portion 3 and has a circular shape in a plan view. The focus ring 10 may be formed of, for example, a material having electrical conductivity equivalent to that of a wafer placed on the mounting surface. By disposing such a focus ring 10, the electrical environment with respect to the plasma at the peripheral portion of the wafer can be made substantially the same as that of the wafer, and differences or biases in the plasma processing between the center and peripheral portions of the wafer can be prevented.
[0115] (Other materials) A power supply terminal 15 for applying a DC voltage to the electrostatic attraction electrode 13 is connected to the electrostatic attraction electrode 13. The power supply terminal 15 is inserted into a through hole 16 that penetrates the temperature control base part 3, the adhesive layer 8, and the support plate 12 in the thickness direction. An insulator 15a having insulating properties may be provided on the outer periphery of the power supply terminal 15, and the power supply terminal 15 is insulated from the metallic temperature control base part 3 by this insulator 15a.
[0116] 2, the power supply terminal 15 is shown as an integrated member. However, the power supply terminal 15 may be configured by electrically connecting a plurality of members. The power supply terminal 15 is inserted into the temperature adjustment base part 3 and the support plate 12, which have different thermal expansion coefficients. For this reason, the portion of the power supply terminal 15 inserted into the temperature adjustment base part 3 (terminal body) and the portion inserted into the support plate 12 (extraction electrode) may be configured from different materials.
[0117] The terminal body of the power supply terminal 15 is preferably made of a metal material such as tungsten (W), tantalum (Ta), molybdenum (Mo), niobium (Nb), or a Kovar alloy.
[0118] The material of the extraction electrode of the power supply terminal 15 is not particularly limited as long as it is a conductive material with excellent heat resistance. The material of the extraction electrode is preferably a material whose thermal expansion coefficient is close to that of the electrostatic attraction electrode 13 and the support plate 12. For example, it is preferably made of a conductive ceramic material such as Al2O3-TaC.
[0119] The terminal body and the extraction electrode may be connected with, for example, a silicone-based conductive adhesive that is flexible and electrically resistant.
[0120] A heater element 5 may be provided on the lower surface side of the electrostatic chuck member 2. The material and shape of the heater element 5 can be selected arbitrarily as long as it is capable of heating the electrostatic chuck member 2. The heater element 5 is preferably a processed non-magnetic thin metal plate having a constant thickness of, for example, 0.2 mm or less, preferably about 0.1 mm.
[0121] The heater element 5 is obtained by processing, for example, a titanium (Ti) thin plate, a tungsten (W) thin plate, a molybdenum (Mo) thin plate, or the like into a desired heater shape by photolithography or laser processing. The shape of the heater element 5 may be, for example, a meandering shape of a strip-shaped conductive thin plate with an overall contour of a ring.
[0122] The heater element 5 may be provided by adhering a non-magnetic thin metal plate to the electrostatic chuck member 2, and then processing and shaping the non-magnetic thin metal plate on the surface of the electrostatic chuck member 2. Alternatively, the heater element 5 may be processed and shaped at a position different from the electrostatic chuck member 2, and then transferred onto the surface of the electrostatic chuck member 2 by printing.
[0123] The heater element 5 is adhered and fixed to the bottom surface of the support plate 12 by an adhesive layer 4 made of a sheet-like or film-like silicone resin or acrylic resin that has uniform thickness, heat resistance, and insulating properties.
[0124] A power supply terminal 17 for supplying power to the heater element 5 is connected to the heater element 5. The power supply terminal 17 may be made of a material similar to that of the power supply terminal 15. The power supply terminals 17 are provided so as to pass through the through holes 3b formed in the temperature adjustment base part 3. The cylindrical insulator 18 is provided between the power supply terminal 17 and the through holes 3b, and is made of an insulating material.
[0125] A temperature sensor 20 may be provided on the lower surface side of the heater element 5. In the electrostatic chuck device 1, an installation hole 21 is formed so as to penetrate the temperature adjustment base part 3 in the thickness direction. The temperature sensor 20 is installed at the top of the installation hole 21. It is desirable to install the temperature sensor 20 in a position as close to the heater element 5 as possible. For this reason, the installation hole 21 may be formed so as to extend further from the structure shown in FIG. 2 so as to protrude toward the adhesive layer 8 side, thereby bringing the temperature sensor 20 and the heater element 5 closer to each other.
[0126] The temperature sensor 20 can be arbitrarily selected from known sensors used for measuring the temperature of a heating element such as the heater element 5. For example, it may be a fluorescent temperature sensor in which a phosphor layer is formed on the upper surface side of a rectangular parallelepiped light-transmitting body made of quartz glass or the like. This temperature sensor 20 is adhered to the lower surface of the heater element 5 with a light-transmitting and heat-resistant silicone resin adhesive or the like.
[0127] The phosphor layer of the temperature sensor 20 is made of a material that emits different fluorescence depending on the heat input from the heater element 5. The material for forming the phosphor layer may be any material that emits fluorescence depending on the temperature of the phosphor layer, and a wide variety of phosphor materials may be selected.
[0128] The material for forming the phosphor layer can be arbitrarily selected from the phosphor materials used in the fluorescent temperature sensor. Examples of such materials include phosphor materials doped with rare earth elements having an energy level suitable for light emission, semiconductor materials such as AlGaAs, metal oxides such as magnesium oxide, and minerals such as ruby and sapphire. Any of these materials can be appropriately selected for use.
[0129] Two or more temperature sensors 20 may be provided as necessary. Each temperature sensor is provided at a position that does not interfere with the power supply terminal or the like and at an arbitrary position in the circumferential direction of the lower surface of the heater element 5.
[0130] The temperature measurement unit 22 measures the temperature of the heater element 5 from the fluorescence emitted by the temperature sensor 20. The temperature measurement unit 22 may be composed of, for example, an excitation unit 23 located outside (below) the installation hole 21 of the temperature adjustment base unit 3 and irradiating the phosphor layer with excitation light, a fluorescence detector 24 detecting the fluorescence emitted from the phosphor layer, and a control unit 25 controlling the excitation unit 23 and the fluorescence detector 24 and calculating the temperature of the heater element 5 based on the detected fluorescence. The temperature measurement unit 22 may have another configuration as long as it measures the temperature of the heater element 5 from the fluorescence emitted by the temperature sensor 20.
[0131] Furthermore, the electrostatic chuck device 1 may have a gas hole 28 provided so as to penetrate from the temperature control base 3 to the mounting plate 11 in the thickness direction thereof. A cylindrical insulator 29 may be provided on the inner periphery of the gas hole 28.
[0132] A gas supply device (cooling means) is connected to the gas hole 28. A cooling gas (heat transfer gas) for cooling the plate-shaped sample W is supplied from the gas supply device through the gas hole 28. The cooling gas is supplied through the gas hole to the grooves 19 formed between the multiple protrusions 11b on the upper surface of the mounting plate 11, and cools the plate-shaped sample W.
[0133] Furthermore, the electrostatic chuck device 1 has a pin insertion hole (not shown) that is provided so as to penetrate from the temperature adjustment base part 3 to the mounting plate 11 in the thickness direction thereof. As the pin insertion hole, for example, a structure similar to that of the gas hole 28 can be adopted. A lift pin for removing the plate-shaped sample is inserted into the pin insertion hole. The electrostatic chuck device 1 has the above-mentioned configuration.
[0134] According to the electrostatic chuck portion and electrostatic chuck device having the above-mentioned configuration, since the above-mentioned compound sintered body is used as the base, it is possible to realize a high electrostatic adsorption force.
[0135] Although various embodiments of the present invention have been described above, the configurations and combinations thereof in each embodiment are merely examples, and addition, omission, substitution, and other modifications of the configurations are possible without departing from the spirit of the present invention. Furthermore, the present invention is not limited to the embodiments. EXAMPLES
[0136] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0137] The methods used in the evaluation are described below.
[0138] <Dielectric constant> In this example, the relative dielectric constant of the compound sintered body was measured by the parallel plate method.
[0139] (Equipment used) Equipment used: Impedance analyzer (model number E4990A, Keysight Technologies), LCR meter (model number 4274A, Keysight Technologies)
[0140] (Measurement conditions) Measurement atmosphere: Air Measurement temperature: 25℃ Measurement frequency: 200Hz, 1MHz
[0141] <Nitrogen content> The amount of nitrogen contained in the composite sintered body was measured by the inert gas fusion-infrared absorption method and the inert gas fusion-thermal conductivity method. The amount of nitrogen contained in the composite sintered body was measured using an oxygen / nitrogen / hydrogen analyzer (LECO, TCH600 model). The nitrogen atom content was calculated from the results.
[0142] <Method for confirming the presence of nitrogen atoms> A bright-field image (BF-STEM image) of the interface between the Al2O3 phase and the SiC particles present at the grain boundaries of the Al2O3 phase in the composite sintered body was taken with a scanning transmission electron microscope (STEM). EDX analysis was performed in the same field of view, and a nitrogen atom peak was confirmed at the interface between the Al2O3 phase and SiC.
[0143] <Volume resistivity (Ω cm)> In this example, the volume resistivity (Ω·cm) of the compound sintered body was measured by the DC three-terminal method.
[0144] (Equipment used) Screen printing machine: MODEL MEC-2400, manufactured by Mitani Micronics Co., Ltd. Resistivity measuring device: Nishiyama Seisakusho Co., Ltd. Digital ultra-high resistance / micro ammeter (Model 5450, manufactured by ADC Corporation)
[0145] (Measurement conditions) Measurement temperature: room temperature (24℃) Measurement atmosphere: Air (flow rate 200ml / min) Applied voltage: 500V
[0146] (Measurement method) Using a screen printer, silver paste (US-202A, manufactured by Daiken Chemical Manufacturing and Sales Co., Ltd.) was printed on the upper and lower surfaces of the sintered body, and then dried in air at 150° C. for 12 hours to form a main electrode 110, a guard electrode 120, and a counter electrode 130, as shown in FIG. 1.
[0147] At this time, the diameter of the main electrode 110 was 1.45 cm, and the inner diameter of the guard electrode 120 was 1.60 cm.
[0148] A DC voltage was applied to the sintered body having the main electrode 110, the guard electrode 120, and the counter electrode 130 formed thereon, and the current after charging for 1 minute was measured to determine the volume resistance (Rv) of the sintered body. Next, the volume resistivity (ρv) was calculated from the thickness of the sintered body and the area of the electrodes according to the following formula (1). ρv = S / t × Rv = S / t × V / I … (1) (S: effective area of electrode (cm 2 ), t: thickness of sintered body (cm), Rv: volume resistance (Ω), V: DC voltage (V), I: current (A)
[0149] <Voltage resistance> In this example, the withstand voltage of the compound sintered body was measured by the following method.
[0150] (Measurement method) A test piece of the 0.3 mm thick composite sintered body was sandwiched between cylindrical electrodes with a diameter of 20 mm. The composite sintered body was then immersed in silicone oil at room temperature, and a high-voltage power supply (manufactured by Matsusada Precision, model number HGR10-20P) connected to the cylindrical electrodes was used to apply a voltage at a rate of 1 kV / sec. The voltage at which a current of 1 μA flows through the test piece was measured as the withstand voltage.
[0151] [Example 1] "Preparation of slurry" As starting materials, β-SiC type silicon carbide (β-SiC) particles having an average particle size of 0.03 μm, which were synthesized by thermal plasma CVD, and aluminum oxide (Al2O3) particles having an average particle size of 0.1 μm were used.
[0152] The β-SiC particles were heat-treated in air at 300°C for 12 hours to oxidize the particle surface. This operation corresponds to the above-mentioned "pre-oxidation step."
[0153] β-SiC particles and Al2O3 particles were weighed out so that the β-SiC particles were 3.0 mass% (3.0 mass parts of β-SiC particles per 100 mass parts of Al2O3 particles) relative to the total amount of Al2O3 particles, and were poured into distilled water containing a polycarboxylic acid-based dispersant to obtain a mixed liquid. This mixed liquid was dispersed using an ultrasonic dispersion device. After this, it was pulverized and mixed using a two-flow particle collision type pulverization and mixing device. This operation corresponds to the above-mentioned "step of obtaining a slurry."
[0154] Nitric acid was added to the resulting mixed solution to adjust the pH of the slurry to 6.5. This operation corresponds to the above-mentioned "pH adjusting step."
[0155] The pH-adjusted slurry was spray-dried in a spray dryer to produce granules containing β-SiC and Al2O3. This operation corresponds to the "step of obtaining granules" in the present invention.
[0156] Next, the granules were heated to 500°C in a nitrogen atmosphere to remove moisture and dispersant (impurities), and then heated at 300°C in an air atmosphere for 12 hours. This operation corresponds to the above-mentioned "oxidation treatment step."
[0157] The granules were then uniaxially press molded at a pressure of 8 MPa to produce a compact measuring 320 mm in diameter and 15 mm in thickness. This operation corresponds to the above-mentioned "molding step".
[0158] The obtained green body was set in a graphite mold and sintered at 1820° C. under a nitrogen atmosphere with a press pressure of 40 MPa to obtain a composite sintered body of Example 1. This operation corresponds to the above-mentioned "pressure sintering step."
[0159] Example 2 A composite sintered body of Example 2 was obtained in the same manner as in Example 1, except that the temperature in the pre-oxidation step was 500° C. and 5.0 parts by mass of β-SiC particles were used in the step of obtaining a slurry.
[0160] Example 3 A composite sintered body of Example 3 was obtained in the same manner as in Example 1, except that the temperature in the pre-oxidation step was 370° C. and 8.5 parts by mass of β-SiC particles were used in the step of obtaining a slurry.
[0161] Comparative Example 1 A compound sintered body of Comparative Example 1 was obtained in the same manner as in Example 1, except that in the pressure sintering step, the nitrogen atmosphere was changed to an argon atmosphere.
[0162] Comparative Example 2 A compound sintered body of Comparative Example 2 was obtained in the same manner as in Example 2, except that in the pressure sintering step, the nitrogen atmosphere was changed to an argon atmosphere.
[0163] Comparative Example 3 A compound sintered body of Comparative Example 3 was obtained in the same manner as in Example 3, except that in the pressure sintering step, the nitrogen atmosphere was changed to an argon atmosphere.
[0164] <evaluation> Fig. 3 is a BF-STEM image of the compound sintered body of Example 3. Fig. 4 is an EDX spectrum obtained by EDX analysis of the interface (indicated by symbol A in Fig. 3) between the Al2O3 crystal grains and the SiC crystal grains in the field of view of Fig. 3. As shown in Fig. 4, at the interface between the Al2O3 crystal grains and the SiC crystal grains, peaks corresponding to aluminum atoms (Al) and oxygen atoms (O) contained in Al2O3, and peaks corresponding to silicon atoms (Si) and carbon atoms (C) contained in SiC, as well as peaks corresponding to nitrogen atoms (N), were detected.
[0165] Similarly, nitrogen atoms were detected at the interface between the Al2O3 crystal grains and the SiC crystal grains in the compound sintered bodies of Examples 1 and 2. On the other hand, no nitrogen atoms were detected in the compound sintered bodies of Comparative Examples 1 to 3. It was confirmed that the compound sintered bodies of Comparative Examples 1 to 3 had nitrogen atom contents below the detection limit.
[0166] The dielectric constant at 200 Hz, the dielectric constant at 1 MHz, the nitrogen content, the volume resistivity, and the withstand voltage were measured for the compound sintered bodies of Examples 1 to 3 and Comparative Examples 1 to 3. The results are shown in Table 1.
[0167] [Table 1]
[0168] By comparing Examples 1 to 3 with Comparative Examples 1 to 3, it was confirmed that the compound sintered bodies of Examples 1 to 3 have a larger relative dielectric constant than the compound sintered bodies of Comparative Examples 1 to 3, which have the same content of SiC as the conductive material and a nitrogen atom content below the detection limit. Since the nitrogen atoms contained in the compound sintered bodies of Examples 1 to 3 were observed at the interface between the Al2O3 phase and the SiC phase, it is presumed that the trace amounts of nitrogen atoms present at the grain boundaries make it easier to form a conductive path, although the details are unclear.
[0169] Moreover, by comparing Examples 1 to 3 and Comparative Examples 1 to 3, it was confirmed that the compound sintered body having a smaller SiC content was superior in withstand voltage.
[0170] Furthermore, by comparing Examples 1 to 3 and Comparative Examples 1 to 3, it was confirmed that a compound sintered body containing 0.015 mass% or more and 0.030 mass% or less of nitrogen and having a silicon carbide content of 7.5 mass% or less has excellent withstand voltage and dielectric constant.
[0171] From the above results, it was confirmed that the present invention is useful. [Explanation of symbols]
[0172] 1...electrostatic chuck device, 11...mounting plate (base), 11a...mounting surface, 12...support plate (base ), 13...electrode for electrostatic adsorption, W...plate-shaped sample
Claims
1. A ceramic composite sintered body including aluminum oxide as a main phase and silicon carbide as a subphase, The compound sintered body further contains nitrogen atoms, The compound sintered body has a nitrogen atom content of 0.015 mass % or more and 0.030 mass % or less.
2. 2. The compound sintered body according to claim 1, wherein the nitrogen atoms are present at interfaces between the aluminum oxide crystal grains and the silicon carbide crystal grains.
3. 3. The compound sintered body according to claim 1, wherein the content of the silicon carbide is 1 part by mass or more and 7.5 parts by mass or less per 100 parts by mass of the aluminum oxide.
4. A plate-shaped substrate using the compound sintered body according to claim 1 or 2 as a forming material, one main surface of which is a mounting surface for mounting a plate-shaped sample; an electrostatic attraction electrode provided on the side of the base opposite to the mounting surface or inside the base.
5. An electrostatic chuck device comprising the electrostatic chuck member according to claim 4 .
Citation Information
Patent Citations
Electrostatic chuck and manufacturing method therefor, and alumina sintered member and manufacturing method therefor
JP2005210077A
Composite sintered body, electrostatic chuck member, electrostatic chuck device, and method for producing composite sintered body
WO2018181130A1